Impending disaster: rise of the epsilon variant in Pakistan and the way forward. Issue 5 (7th October 2021) - Moin, Alina; Usmani, Shajie Ur Rehman; Khan, Hashim
Abstract: The constantly mutating severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) does not appear to be slowing down any time soon. All countries, particularly developing countries, must adapt and strategically plan their way of life around the pandemic, while doing everything possible to keep the mortality rate and spread of the newly emerging variants as low as possible, in order to avoid a further blow to the economy and way of life. Pakistan is one such developing country that is currently battling the dangerous delta strain of SARS-COV-2 with limited resources and has recently seen the emergence of an equally transmissible and highly infectious epsilon strain. This is a concerning situation considering that Pakistan's already overburdened health system and faltering economy cannot withstand another dangerous SARS-COV-2 variant attack. This article highlights some strategies for the country to fortify its defences to prevent the epsilon variant from spreading before it is too late, and emphasises that while identifying potential immune evasion mechanisms in SARS-COV-2 variants is critical in the fight against COVID-19, it is also critical to develop methods of efficient and cost-effective detection to identify an early outbreak and then vigilantly and systematically plan area lockdowns before any hope of conquering this pandemic is lost.